An inexpensive method for the automation of biomass measurements in lab-scale bioreactors. - Hamilton R; Casasús-Zambrana A; Svoronos SA; Koopman B (JALA: Journal of the Association for Laboratory Automation, 2005)
An automated online sampling and measurement system that can be assembled for less than $5000 in components (including spectrophotometer, pump, computer, valves, and relays) is described. The public domain Visual Basic source code that we developed is posted at http://www.ees.ufl.edu/homepp/koopman/hamilton_etal/. This system has proven to be very successful for measuring biomass in long-duration (36h) experiments. In addition to providing a measurement record, this system could also be part of an automatic process control system.